Peran Kepemimpinan dalam Membangun Budaya Kerja(Studi pada PT. Lunaray Cahya Abadi Bandung) - Aura Syahida Andryanti N; Linda Agustin; Luqman Nur Zaman; Intan Reynanti; Hani Humaeriyah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study is motivated by the importance of leadership in building a work culture that supports quality, safety, and organizational performance, particularly in companies with strict operational standards. This study aims to analyze the role of leadership in building work culture at PT. Lunaray Cahya Abadi through the implementation of hygiene procedures, use of personal protective equipment, health monitoring, and enforcement of work discipline. This research employs a qualitative approach with a case study design, using interviews with management and analysis of company work culture procedure documents. The findings indicate that leadership plays a significant role in shaping work culture through standard setting, role modeling, communication, and consistent supervision. Work culture procedures function not only as technical guidelines but also as instruments for shaping disciplined, responsible, and quality-oriented work behavior. The study concludes that the effectiveness of work culture is strongly influenced by the active role of leadership in internalizing organizational values and ensuring compliance with procedures. The implications of this study highlight leadership as a key driver in developing a sustainable work culture that supports organizational performance